Golden and brown flaxseed (Linum Usitatissimum L.) physicochemical and microbiological characterization - Novello, Diana (2012)
This study evaluated the physicochemical and microbiological characteristics of oil and seed from golden and brown flaxseed, marketed in Brazil. The physicochemical composition, fatty acid profile, microbiological quality and stability to lipid oxidation in oils samples from golden and brown flaxseed were determined. No difference in the physicochemical composition was found in oil samples from golden and brown flaxseed. The total saturated fatty acids (SFA) contents were higher in oil from brown flaxseed. As for the total monounsaturated fatty acids (MUFAs) contents in both samples, no significant difference was detected. The total polyunsaturated fatty acids (PUFAs) contents and the PUFAs/SFA ratio were higher in golden flaxseed oil. The moisture, lipids, proteins and calories amounts in brown flaxseed seed were higher than those found in the golden variety. The total SFA was higher in seed from brown flaxseed, and no statistical differences were found between MUFAs and PUFAs contents. The lower PUFAs/SFA ratio was observed in seed from brown flaxseed. The microbiological quality was satisfactory, and being in accordance with the security parameters. The analyzed oils showed low concentrations of malonaldehyde. The golden flaxseed showed a better nutritional profile, mainly due to its fatty acid composition.